Differentiation of Friend erythroleukemia cells induced by benzodiazepines. - Wang, J K (1984)
Many benzodiazepines of the type whose receptors are found in peripheral tissues cause the differentiation of cultured Friend erythroleukemia cells. The maximal level of induction of hemoglobin synthesis is 10-80% of the cells, depending on the compound tested. The induction is concentration and time dependent, requiring micromolar amounts of the drugs and about 5 days of treatment for full expression. The time course is very similar to that observed for a well-studied inducer, dimethyl sulfoxide. The affinities of the agents for the peripheral-type benzodiazepine binding site are not correlated with their capacity to induce differentiation. Also, the biological effect is stereospecific since the (3S) stereoisomer Ro11 -6896 is at least an order of magnitude more potent than its (3R) enantiomer, Ro11 -6893. The benzodiazepine effect exhibits definite structure-activity relationships. A 1-methyl group is an absolute requirement, although this is not sufficient in itself. Hydroxyl and methoxyl groups at the 4' position enhance the biological activity, but 4'-chloro decreases it. Substitutions at the 2', 6', and 4 positions also decrease the biological activity, as does the lack of a 2-carbonyl group. These data suggest that the benzodiazepines act in a specific manner to induce the differentiation of Friend erythroleukemia cells.